Comparison of Phospholipid-Based Particles for Sustained Release of Ciprofloxacin Following Pulmonary Administration to Bronchiectasis Patients - Jeffry Weers (Pulmonary Therapy, 2019)
Abstract The rapid clearance of ciprofloxacin hydrochloride from the lungs following administration as an aerosol leads to poor efficacy in the treatment of pulmonary infections. The development of formulations capable of sustaining ciprofloxacin concentrations in the lungs has the potential to significantly improve antibacterial activity. The present review compares two approaches for sustaining levels of ciprofloxacin in the lungs, a liposomal formulation where ciprofloxacin is encapsulated in small unilamellar vesicles, and a dry powder formulation of the practically insoluble zwitterionic form of the drug. These two formulations recently completed large multicenter, phase 3 clinical studies in bronchiectasis patients. As such, they present a unique opportunity to examine the chemistry, manufacturing, and control of the dosage forms in addition to their tolerability and efficacy in more than 1000 bronchiectasis patients. Both formulations were generally well tolerated with most adverse events found to be mild to moderate in intensity. While the formulations were effective in reducing and/or eradicating infections, this did not lead to reductions in pulmonary exacerbations, the primary endpoint. The failures speak more to the heterogeneous nature of the disease and the difficulty in identifying bronchiectasis patients likely to exacerbate, rather than an inherent limitation of the formulations. While the formulations are similar in many respects, they also present some interesting differences. This review explores the implications of these differences on the treatment of respiratory infections.